Infrastructure Funds - Voldan, Marion (2022)
This paper analyzes how infrastructure fund values evolve over their lifetime. I calculate three different quarterly performance metrics over the life of each fund, using the reported net asset values (NAVs) and the stream of future cash flows. Based on a sample of 119 mature closed-end private equity infrastructure funds from Preqin, I find a high value dispersion for funds of all ages, and this dispersion tends to increase towards the end of the fund life. An examination of the cross-sectional determinants of the remaining performance reveals the following: first, a high to-date distribution to paid-in capital (DPI) ratio is a significant positive predictor of remaining fund performance. Second, a high amount of market dry powder hurts the performance of Young funds but benefits older funds. Third, there is a negative relationship between GDP growth and remaining fund performance. Last, a widening credit spread hurts future performance, probably due to high lending costs. I additionally study how the reported NAVs compare to a target return range of 10% to 15% over the life of each fund, based on the actual cash flows. I find that a discount needs to be applied to the NAV for most of the sample. Using a target return of 12%, the median discount over the fund age of 4 - 9 years is 8% - 29%. My findings align with the discounts observed in secondary market transactions, which range from 10% - 30%.